2019
DOI: 10.14336/ad.2018.0224
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Hypothyroidism and Endometrial Cancer

Abstract: Thyroid dysfunction is involved in several types of carcinoma. Hypothyroidism is one of the most common medical morbidities among patients with endometrial cancer; however, the related mechanism is unclear. Among the risk factors related to endometrial cancer, hypothyroidism interacts with metabolic syndrome, polycystic ovarian syndrome and infertility or directly acts on the endometrium itself, which may influence the development and progression of endometrial cancer. We summarize recent studies on the relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 52 publications
0
20
1
5
Order By: Relevance
“…Several studies have shown that hypothyroidism is closely related to MS, PCOS, elevated serum leptin levels, and dyslipidemia. Hypothyroidism may promote the occurrence and development of endometrial cancer by indirectly increasing the risk factors of endometrial cancer or through direct interaction (123). Studies examining the relationship between thyroid function (TSH level) and endometrial cancer will provide new insights into the mechanism of endometrial cancer.…”
Section: Other Types Of Diseases Of Metabolic Syndrome and Endometriamentioning
confidence: 99%
“…Several studies have shown that hypothyroidism is closely related to MS, PCOS, elevated serum leptin levels, and dyslipidemia. Hypothyroidism may promote the occurrence and development of endometrial cancer by indirectly increasing the risk factors of endometrial cancer or through direct interaction (123). Studies examining the relationship between thyroid function (TSH level) and endometrial cancer will provide new insights into the mechanism of endometrial cancer.…”
Section: Other Types Of Diseases Of Metabolic Syndrome and Endometriamentioning
confidence: 99%
“…In recent times, a strong association between primary malignancies of thyroid and melanoma has been established [ 116 ]. At the same time increased TSH level is associated with poor prognosis for endometrial carcinoma patients [ 117 ]. A meta-analysis study reported an elevated risk of colorectal cancer in patients with hypothyroidism and thyroid replacement therapy has a protective role [ 118 ].…”
Section: Disorders and Diseases Associated With Thyroid Dysfunctionmentioning
confidence: 99%
“…All these factors were evident in the best “four-factor” model for the primary female infertility ( Supplementary Note ). The influence of elevated TSH and LH/FSH ratio may also lead to the formation of myometrial and endometrial hyperplasia in forms of polyp/tumour [44,45], which cause infertility in females by bleeding, blocking or obliterating the passage of sperm conduction [46,47]. Besides, collection of fluid in the POD is generally associated with infection [48,49], rupture of cyst [50], and ectopic pregnancy [51], contributing to female infertility, and so, these two radiologically diagnosed factors were identified as significant risk factors for female infertility in this study.…”
Section: Discussionmentioning
confidence: 99%